Effect of root exudates of Eucalyptus urophylla and Acacia mearnsii on soil microbes under simulated warming climate conditions - Wu, Jiahui (BMC Microbiol, 2019)
BACKGROUND: Recent studies demonstrated that warming and elevated carbon dioxide (CO(2)) indirectly affect the soil microbial community structure via plant root exudates. However, there is no direct evidence for how the root exudates affect soil microbes and how the compositions of root exudates respond to climate change. RESULTS: The results showed that warming directly decreased biomass of soil-borne bacteria and fungi for Acacia mearnsii De Willd but it did not impact soil microbial community for Eucalyptus urophylla S.T. Blake. In contrast, elevated CO(2) had strong direct effect on increasing soil microbial biomass for both plant species. However, plant roots could significantly increase the secretion of antibacterial chemicals (most probable organic acids), which inhibited the growth of bacteria and fungi in elevated CO(2) environment. This inhibitory effect neutralized the facilitation from increasing CO(2) concentration on microbial growth. CONCLUSIONS: We concluded that climate change can directly affect microorganisms, and indirectly affect the soil microbial community structure by changes in composition and content of plant root exudates.